Multiplicity of Entrepreneurship : An Analysis of Chinese, Malay and Indian Entrepreneurs in Malaysia. - Chin, Yee Whah; Ong, Beng Kok (2011)

(untitled)
The paper is based on an ongoing research project. It aims to provide a descriptive account on the concept of entrepreneurship in a multicultural, multilingual and multi religious society of Malaysia. The research traces the sources of influence on the emergence and development of entrepreneurship, link types of entrepreneurship to levels of sustainability and types of business activities.